Analisis Fungsi Pengawasan Wali Pemasyarakatan dalam Proses Asimilasi, Pembebasan Bersyarat dan Cuti Menjelang Bebas: Studi Kasus di Rumah Tahanan Kelas I Pondok Bambu - FITRIANINGSIH FITRIANINGSIH; WARSIFAH WARSIFAH (Indonesian Journal of Social Science Education (IJSSE), 2023)
This article discusses the function of correctional guardians in general and examines in more depth their role ini the process of assimilation, parole and leave for release for prisoners studied at the Pondok Bambu Class I Detention Center. This research was conducted using qualitative descriptive analysis method with a juridical approach. Data was collected through in-depth interview and literature study and then analyzed using interactive model. The resrach results show that there are still prisoners who do not exercise their right in the assimilation, conditional release and leave for release programs. Several influencing factors are grouprd into three factors, namely awareness factor in exercising their right, whether the prisoner has sufficient knowledge or not then procedural and technical factors. From the facts researched, it focuses on the study regarding when the correctional guardians duties as a companion are directly related to the process of fulfilling the rights of correctional inmates, where the role as facilitator, communicator and motivator for prisoners during the development process in carried out in accordance with the rules, able to encourage increased fulfillment of right. This then an inpact on reducing the risk of excess capacity at the Pondok Bambu Class I Detention Center. In the end, this paper in expected to axplain the meaning, duties, obligations and authotority as well as analysis regarding roles and implementation as well as field facts which ultimately provide conslusions and suggestions that will be useful for fulfuling the rights or inmates in correctional facilities and maximizing the task of mentoring in term of coaching and mentoring inmates as intended mandated by law.